Derivation of Effective Guidance for Specification Constructions from CDFD-based Knowledge Representation - Abdul Rahman, Mat; Shaoying, Liu (IEEE, 2013)
A completeness and accurateness of a specification is depend on how appropriateness and relevancy of the questions during a process of developing the specification. The process of providing an effective question requires several stages and need more discussions between system analyst and knowledge engineer. In this paper, we present on the structure of the questions in which are based on Context Data Flow Diagram (CDFD). In order to describe on how this method can be applied to derive an effective guidance, we use a case study of a brain tumor treatment system to assist and guide system analyst to construct the specification. Our aim is to develop a knowledgebased supporting tool to help system analyst in constructing formal specification.